Engineering hepatitis B virus core particles for targeting HER2 receptors in vitro and in vivo - Mohamed Suffian, Izzat Fahimuddin; Wang, Julie Tzu-Wen; Hodgins, Naomi O.; Klippstein, Rebecca; Garcia-Maya, Mitla; Brown, Paul; Nishimura, Yuya; Heidari, Hamed; Bals, Sara; Sosabowski, Jane K.; Ogino, Chiaki; Akihiko, Kondo; et al. (Elsevier, 2017)
Hepatitis B Virus core (HBc) particles have been studied for their potential as drug delivery vehicles for cancer therapy. HBc particles are hollow nano-particles of 30–34 nm diameter and 7 nm thick envelopes, consisting of 180–240 units of 21 kDa core monomers. They have the capacity to assemble/dis-assemble in a controlled manner allowing encapsulation of various drugs and other biomolecules. Moreover, other functional motifs, i.e. receptors, receptor binding sequences, peptides and proteins can be expressed. This study focuses on the development of genetically modified HBc particles to specifically recognise and target human epidermal growth factor receptor-2 (HER2)-expressing cancer cells, in vitro and in vivo, for future cancer therapy. The non-specific binding capacity of wild type HBc particles was reduced by genetic deletion of the sequence encoding arginine-rich domains. A specific HER2-targeting was achieved by expressing the ZHER2 affibodies on the HBc particles surface. In vitro studies showed specific uptake of ZHER2-ΔHBc particles in HER2 expressing cancer cells. In vivo studies confirmed positive uptake of ZHER2-ΔHBc particles in HER2-expressing tumours, compared to non-targeted ΔHBc particles in intraperitoneal tumour-bearing mice models. The present results highlight the potential of these nanocarriers in targeting HER2-positive metastatic abdominal cancer following intra-peritoneal administration.